2017
DOI: 10.1097/pep.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and Serious Games in Neurorehabilitation of Children and Adults: Prevention, Plasticity, and Participation

Abstract: Use of virtual reality (VR) and serious games (SGs) interventions within rehabilitation as motivating tools for task specific training for individuals with neurological conditions are fast-developing. Within this perspective paper we use the framework of the IV STEP conference to summarize the literature on VR and SG for children and adults by three topics: Prevention; Outcomes: Body-Function-Structure, Activity and Participation; and Plasticity. Overall the literature in this area offers support for use of VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 147 publications
1
55
0
3
Order By: Relevance
“…A new trend within the telerehab sector is the development of applications through multimedia and gamification techniques in the rehabilitation of patients with physical disabilities. One example is "Rehab@Home," which is an infrastructure based on commercially available and relatively low-cost devices, such as "Kinect" or "Nintendo Wii," creating a virtual environment for the patient, and uses "exergames" that increase the engagement of rehabilitation [22]. Additionally, OPTI-RERC -Optimizing Participation Through Technology for Successful Aging with Disability -is a project that is providing VR and gamification in the home-based motor assessment.…”
Section: Review Technology and Technical Featuresmentioning
confidence: 99%
“…A new trend within the telerehab sector is the development of applications through multimedia and gamification techniques in the rehabilitation of patients with physical disabilities. One example is "Rehab@Home," which is an infrastructure based on commercially available and relatively low-cost devices, such as "Kinect" or "Nintendo Wii," creating a virtual environment for the patient, and uses "exergames" that increase the engagement of rehabilitation [22]. Additionally, OPTI-RERC -Optimizing Participation Through Technology for Successful Aging with Disability -is a project that is providing VR and gamification in the home-based motor assessment.…”
Section: Review Technology and Technical Featuresmentioning
confidence: 99%
“…stroke, traumatic brain injury, spinal cord injury, cerebral palsy, multiple sclerosis, etc.) (Deutsch & McCoy, 2017; Howard, 2017; Klamroth-Marganska et al, 2014; Lange et al, 2012; Merians et al, 2010), and for the assessment and rehabilitation of attention, memory, spatial skills, and other cognitive functions in both clinical and unimpaired populations (Bogdanova, Yee, Ho, & Cicerone, 2016; Matheis et al, 2007; Parsons, Rizzo, Rogers, & York, 2009; Pugnetti et al, 1995; Rizzo, 1994; Rizzo et al, 2006; Valladares-Rodriguez et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Recent neuroimaging studies too have reaffirmed these aspects, as VR-based interventions were shown to instigate neural plasticity. [25][26][27][28][29] In addition, other mechanisms that have been proposed to facilitate recovery using VR include enhanced biomechanical efficiency, real-time error feedback, 30,31 increased arousal, 32 and motivation. 33 Recently published systematic reviews have recommended the use of VR as a tool for gait rehabilitation poststroke.…”
Section: Introductionmentioning
confidence: 99%